Rescue and personal involvement: a response to Woollard - Pummer, T; Crisp, R (Oxford University Press, 2019)
Fiona Woollard argues that when one is personally involved in an emergency, one has a moral requirement to make substantial sacrifices to aid others that one would not otherwise have. She holds that there are three ways in which one could be personally involved in an emergency: by being physically proximate to the victims of the emergency; by being the only person who can help the victims; or by having a personal encounter with the victims. Each of these factors is claimed to be defeasibly sufficient to ground personal involvement, and thus a requirement of substantial sacrifice to aid. Woollard defends this view on the basis of a number of cases. We show that Woollard's cases contain various confounding factors. In view of the more precisely drawn cases offered here, it is clear that neither proximity nor uniqueness nor personal encounter is intuitively defeasibly sufficient in the way Woollard claims.